Collaboration in Healthcare Through Boundary Work and Boundary Objects - Meier, Ninna (Qualitative Sociology Review, 2015)
This article contributes to our understanding of how boundary work is practiced in healthcare settings. Previous studies have shown how boundaries are constantly changing, multiple, and co-existing, and can also be relatively stable cognitive and social distinctions between individuals and groups. In highly specialized, knowledge-intensive organizations such as healthcare organizations, organizational, professional, and disciplinary boundaries mark the formal structure and division of work. Collaboration and coordination across these boundaries are essential to minimizing gaps in patient care, but also may be challenging to achieve in practice. By drawing on data from an ethnographic study of two hospital wards, this article investigates practices of cross-disciplinary and professional collaboration and adds to our knowledge of how this kind of boundary work is produced in context. Moreover, it adds to existing boundary literature by exploring the fast-paced, situational, micro-interactions in which boundaries are drawn, maintained, and dissolved. These mundane, brief exchanges are essential to the practice of collaboration through boundary work. I consider the implications of these findings for boundary theory and boundaries in healthcare and other related settings.